Novel experimental setup for megahertz X‐ray diffraction in a diamond anvil cell at the High Energy Density (HED) instrument of the European X‐ray Free‐Electron Laser (EuXFEL). (2nd May 2021) - Liermann, H. P.; Konôpková, Z.; Appel, K.; Prescher, C.; Schropp, A.; Cerantola, V.; Husband, R. J.; McHardy, J. D.; McMahon, M. I.; McWilliams, R. S.; Pépin, C. M.; Mainberger, J.; et al.
Abstract : The high‐precision X‐ray diffraction (XRD) setup for work with diamond anvil cells (DACs) in Interaction Chamber 2 of the High Energy Density (HED) instrument of the European X‐ray Free‐Electron Laser is described. Abstract : The high‐precision X‐ray diffraction setup for work with diamond anvil cells (DACs) in interaction chamber 2 (IC2) of the High Energy Density instrument of the European X‐ray Free‐Electron Laser is described. This includes beamline optics, sample positioning and detector systems located in the multipurpose vacuum chamber. Concepts for pump–probe X‐ray diffraction experiments in the DAC are described and their implementation demonstrated during the First User Community Assisted Commissioning experiment. X‐ray heating and diffraction of Bi under pressure, obtained using 20 fs X‐ray pulses at 17.8 keV and 2.2 MHz repetition, is illustrated through splitting of diffraction peaks, and interpreted employing finite element modeling of the sample chamber in the DAC.